VALIDITAS LKS BERBASIS KETERAMPILAN PROSES BERORIENTASI LINGKUNGAN SEKITAR PADA SUBMATERI ARTHROPODA UNTUK KELAS X - NURSADIYAH, NITAMAYA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
This study aimed to know and describe the validity of student worksheet based on process skills and environment oriented of subsubject Arthropod for grade X of senior high school that developed. The validity of student worksheet was reviewed based on the result of the validation conducted by two experts of learning materials and educational biologi, and also two biology teacher. The validity of student worksheet was 3,58 (very feasible). Based on the results the students worksheet were feasible in terms of validity. Key words: Validity, student worksheet, skills process, environment oriented, subsubject Arthropod.